Preparation and Characterization of Ti-15Mo Alloy used as Biomaterial - Severino Martins Junior, Jose Roberto [UNESP]; Nogueira, Renata Abdallah [UNESP]; de Araujo, Raul Oliveira [UNESP]; Goto Donato, Tatiani Ayako; Arana-Chavez, Vitor Elias; Rosifini Alves Claro, Ana Paula [UNESP]; Silos Moraes, Joao Carlos [UNESP]; Rabelo Buzalaf, Marilia Afonso; Grandini, Carlos Roberto [UNESP] (Universidade Federal de São Carlos (UFSCar), Dept Engenharia Materials, 2011)
With the increase in life expectancy, biomaterials have become an increasingly important focus of research because they are used to replace parts and functions of the human body, thus contributing to improved quality of life. In the development of new biomaterials, the Ti-15Mo alloy is particularly significant. In this study, the Ti-15Mo alloy was produced using an arc-melting furnace and then characterized by density, X-ray diffraction, optical microscopy, hardness and dynamic elasticity modulus measurements, and cytotoxicity tests. The microstructure was obtained with beta predominance. Microhardness, elasticity modulus, and cytotoxicity testing results showed that this material has great potential for use as biomaterial, mainly in orthopedic applications.
Keywords: Ti-Mo alloys; elasticity modulus; biomaterials; vacuum melting